A researcher's guide to the National Statistics Socio-economic Classification - Rose, David, 1947 February 17-; Pevalin, David J. (SAGE, 2003)
Required reading for all users of government social classifications this volume evaluates how well the new system of socio-economic classification works in describing and explaining the relationships between social classes and key health and employment variables.